WWC proteins as emerging biomarkers and therapeutic targets in cancer pathogenesis - Wang, Shuge; Li, Junzhe; Xu, Xianhua; Xu, Shijie (Frontiers in Cell and Developmental Biology, 2026)
WW and C2 domain-containing (WWC) proteins have emerged as pivotal regulators of cancer initiation, progression, and therapeutic resistance. This review synthesizes current evidence demonstrating that WWC1, WWC2, and WWC3 exert context-dependent effects across malignancies, with WWC2 consistently functioning as a tumor suppressor while WWC1 and WWC3 display tissue-specific variability. By integrating and regulating multiple signaling pathways, particularly Hippo and Wnt, WWC proteins function as molecular scaffolds that regulate proliferation, apoptosis, epithelial-mesenchymal transition, and metastasis. This review provides a comprehensive overview of the molecular characteristics, biological functions, and clinical implications of WWC proteins, highlighting their potential as prognostic biomarkers and therapeutic targets for precision oncology.